Empowering the young reader: An educational perspective on developing foundational reading skills - Al-Barakat, Ali Ahmad; Al-Qatawneh, Sami Sulieman; AlAli, Rommel Mahmoud; Al-Hassan, Omayya M.; El-Mneizel, Abdalla Falah; Abdullatif, Ali K.; Ismail, Abdelrahim Fathy; El-Shamy, Hemdan (Research Journal in Advanced Humanities, 2026)
This study investigates the perspectives of preschool educators in Amman, Jordan, regarding the importance of specific reading skills for preschool learners. It aims to prioritize reading skills according to teachers’ perceptions and to identify any variations based on their educational qualifications. Utilizing a quantitative research design, the study employed a detailed 32-item questionnaire designed through literature reviews and expert consultations in early childhood education. A sample of 690 teachers responded to the survey, revealing that skills related to reading comprehension and expression were deemed most significant. Key skills identified include recalling textual details and using specific vocabulary in everyday conversations. In contrast, teachers rated higher-level language skills as less important, reflecting their consideration of preschoolers’ developmental readiness. The study’s findings, supported by a one-way ANOVA, indicated no significant differences in perceptions among teachers based on academic qualifications, suggesting a common ground in teaching practices and professional growth. It emphasizes the necessity for integrating more complex interactive language skills into early childhood curricula and preparing teachers accordingly. Furthermore, the research advocates for ongoing professional development to foster independent critical thinkers among young learners and calls for more qualitative and mixed-methods studies to deepen the understanding of early literacy development across diverse teaching contexts.